The comparative study of some faba bean (Vicia faba L.) varieties under rainfed condition in Sulaimani –Iraqi Kurdistan Region. - Tofiq, Sherwan Esmail; Aziz, Omer Kerim; Salih, Sazgar Hama (Sulaimani Journal for Pure and Applied Sciences, 2015)
The present study was carried out at Sulaimani region- Agricultural Research Center of Bakrajo, during three successive winter seasons (2011-2014).Using seven varieties of faba bean namely Zaina, Seher, Yieldiz, Civilla, Luz di Otono , Tanyari, and local. According to randomized complete block design with three replications. The comparisons among the means were carried out using least significant difference test (LSD) at 0.05 significant level. Results of this investigation summarized as the average of all seasons as follow: The variety Seher recorded maximum values for the characters pod length, number of seeds per pod and 100 seed weight, while the variety Civilla recorded the highest value for the characters number of seeds per plant and seed yield, while local variety produced the highest value for the character number of pods per plant. Significant differences were presented between seasons due to the average of all characters. The third season exhibited maximum values due to the characters number of pods per plant, pod length, number of seeds per plant and seed yield.
Keywords: Broad bean Variety Environment